Case report: Candidiasis of gastrojejunostomosis after pancreaticoduodenectomy: Preliminary experience from two cases - Nguyen, Thanh Khiem; Nguyen, Ham Hoi; Nguyen, Cong Long; Luong, Tuan Hiep; Dinh, Long Doan; Le, Van Duy; Dang, Kim Khue; Tran, Thi Lan (Frontiers in Oncology, 2022)
Introduction Invasive Candida infection, or candidiasis, especially in gastrointestinal tract (GIT) is an infrequent but aggressive disease caused by Candida species. Candidiasis of gastrojejunostomosis after extensive gastrointestinal surgery may cause serious complications such as perforative peritonitis and anastomotic stenosis, which requires surgical interventions. Case presentation Our two patients had undergone pancreaticoduodenectomy (PD), respectively, due to pancreatic ductal adenocarcinoma and intraductal papillary mucinous neoplasms of the pancreatic head. Both the patients were malnutritioned and debilitated before the surgery, and they required reoperation for postoperative Candidiasis-relevant complication.In the first case, the patient was readmitted to the hospital with symptoms of perforative peritonitis, for which he underwent surgery and had Candida found in both gastrojejunostomosis ulcer and peritoneal fluid. In our second case, the patient was admitted to the hospital twice after the first operation and diagnosed with Candida-induced gastrojejunostomosis stenosis by esophagogastroduodenoscopy (EGD) and endoscopic biopsy. Fluconazole was indicated for a 2-week regimen. Blood sample withdrawn afterward showed no evidence of fungal agents, and the anastomotic stenosis responded well to treatment. However, after 3 weeks, he came back with cachexia and symptoms of gastrojejunostomotic stenosis. EGD showed no image of fungal agents but anastomotic stenosis due to chronic inflammatory process. The patient was then reoperated to redo his gastrojejunostomosis. Conclusion Candidiasis of gastrojejunostomosis after extensive gastrointestinal surgery such as PD is a very aggressive condition that may cause perforative peritonitis and anastomotic stenosis. However, there have been no publications on this disorder, and the strategic treatment remains unknown. We hereby present a report of two cases with postoperative gastrojejunostomosis candidiasis presenting with non-specific but aggressive and early clinical symptoms.